Electrocardiographic differences between Anderson-Fabry and sarcomeric hypertrophic cardiomyopathy and correlation with cardiac magnetic resonance. (25th November 2020) - Vitale, G; Di Nicola, F; Tanini, I; Camporeale, A; Graziani, F; Ditaranto, R; Zanoni, R; Ferrara, V; Lombardi, M; Olivotto, I; Rapezzi, C; Galie, N; et al.
Abstract: Background: Differential diagnosis between Anderson-Fabry (AF) and sarcomeric hypertrophic cardiomyopathy (HCM) is often very challenging particularly in AF patients with late onset cardiac involvement. Purpose: To gain new insights from standard electrocardiogram (ECG) in AF disease for differential diagnosis from sarcomeric HCM. Additionally, to better understand ECG features in AF patients, a correlation substudy ECG-cardiac magnetic resonance (CMR) has been performed. Methods: From 162 patients with definite diagnosis of AF disease, 111 [65 males, median age 57 (51–67) years] with pathologic left ventricular hypertrophy (LVH) (Group A) were compared with 111 sarcomeric HCM patients (Group B) sex, age and maximal wall thickness matched by 1:1 propensity score. Results: AF patients showed shorter PR interval [155 (140–180) vs 163 (149–184) msec; p=0.005) and wider QRS interval [110 (100–134) vs 100 (90–106) msec; p<0.0001). Additionally AF patients had a higher prevalence of complete (22% vs 3%; p<0.0001) and incomplete (13% vs 1%; p<0.0001) right bundle branch block (RBBB) and a higher percentage of ST segment depression (12% vs 1%; p=0.001) and inferior negative T waves (34% vs 19%; p=0.01). No differences in terms of Sokolow-Lyon and Cornell scores were found whereas total QRS score was higher in Group A [20 (16–27) vs 18 [14–22] mV; p=0.0004). Low QRS voltages and inferior Q waves were not present in AF patients. Among the 69 AF patients who underwent MRI, the 44 with late gadolinium enhancement (LGE) were older [59 (52–66) vs 53 (40–59) years; p=0.017] and had more frequently negative T waves on ECG, particularly in the inferior leads (64% vs 8%; p<0.0001), compared to the 25 without LGE. At multivariate analysis, age and negative T waves were independently associated to the presence of LGE on CMR. Conclusions: Compared to matched sarcomeric HCM, AF patients had a shorter PR, wider QRS and a higher percentage of RBBB in relation to to the different aetiology (storage vs "pure" hypertrophy). The higher total QRS score and the absence of inferior Q waves could reflect the more frequent concentric distribution of LVH. Additionally negative T waves, especially in inferior leads, are related to the presence of LGE on CMR (often in the postero-lateral wall). Funding Acknowledgement: Type of funding source: None